Frankenstein - McFadden, Deanna; Akib, Jamel; Shelley, Mary Wollstonecraft, 1797-1851. (New York : Sterling Pub., 2006)
An abridged version of the novel in which a monster assembled by a scientist from parts of dead bodies develops a mind of his own as he learns to loathe himself and hate his creator.
4.0
3-6
3-6
Keywords: Horror stories; Monsters -- Fiction; Horror fiction; Monsters -- Fiction